Evaluation of left ventricular global function, using Doppler Myocardial Performance Index (Tei- index) in patients with systemic Hypertension - Sarkar, H; Siddique, MA; Ahmed, CM; Ahmed, MK; Mahmood, M; Ahsan, SA; Salman, M; Habib, SMA; Haque, KMHS S (University Heart Journal, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> The study was designed to compare the Doppler myocardial performance index (Tei index) between those patients with systemic hypertension with normal populations. 50 patients with hypertension (16 with left ventricular hypertrophy and 34 without hypertrophy) were taken as cases and 52 age and sex matched healthy individuals were taken as controls. Left ventricular global function was calculated using the echocardiographic Doppler index as described by Tei et al. (Tei index). Left ventricular global function differs significantly between those with left ventricular hypertrophy and without hypertrophy. Pulmonary venous flow parameters revealed significant increase in atrial reversal velocity (AR velocity) and also significant lengthening of atrial reversal duration (AR duration). All of these parameters signify worsening diastolic properties. The Tei index is not affected by increasing age and therefore, is appropriate for evaluating left ventricular global function in hypertensive patients, most of whom are middle aged or older. This index may be useful for determining treatment strategy and evaluating treatment effects. Â University Heart Journal Vol.4(1) January 2008